2006
DOI: 10.1080/02770900500448803
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Case-Control Study on the Effect of Bronchial Asthma During Pregnancy for Congenital Abnormalities of the Offspring

Abstract: Bronchial asthma is one of the most common maternal diseases complicating pregnancy. We assessed the risks of congenital abnormalities in a case-control population-based analysis using the dataset of the Hungarian Case-Control Surveillance of Congenital Abnormalities between 1980 and 1996. Of the 22,843 cases with congenital abnormalities, 511 (2.2%) had mothers with bronchial asthma, while of the 38,151 matched control subjects without congenital abnormalities 757 (2.0%) had mothers with bronchial asthma (una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 17 publications
2
48
0
1
Order By: Relevance
“…In the study by Tata et al based on 704 cases of malformation born to women with asthma, there were 44 comparisons with hypothesis testing and two comparisons (circulatory system: OR 5 1.20 [95%CI:1.01-1.43] and musculoskeletal malformations: OR 5 1.25 [95%CI:1.06-1.47]) were found to be significant at the 5% and the 1% level, respectively (Tata et al, 2008). Similarly, in the study by Tamasi were found to be significant both at the 5% level (Tamasi et al, 2006). However, neither of these two studies has made adjustments for multiple testing.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…In the study by Tata et al based on 704 cases of malformation born to women with asthma, there were 44 comparisons with hypothesis testing and two comparisons (circulatory system: OR 5 1.20 [95%CI:1.01-1.43] and musculoskeletal malformations: OR 5 1.25 [95%CI:1.06-1.47]) were found to be significant at the 5% and the 1% level, respectively (Tata et al, 2008). Similarly, in the study by Tamasi were found to be significant both at the 5% level (Tamasi et al, 2006). However, neither of these two studies has made adjustments for multiple testing.…”
Section: Discussionmentioning
confidence: 55%
“…However, most of these studies were underpowered and were conducted over 20 years ago resulting in the use of older asthma therapies not reflective of current asthma treatment. Regarding the three case-control studies, two of them assessed the composite outcome as well as the risk for specific congenital malformations (Tamasi et al, 2006;Tata et al, 2008) while the third one only evaluated the risk for heart defects (Lin et al, 2009). Only one study showed a greater (although small) risk for any congenital malformation (OR 5 1.10; 95%CI: 1.01-1.20) (Tata et al, 2008), but all of them found a greater risk for at least one group of specific malformations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations